Functional dissection of N-terminal nuclear trafficking signals of SETDB1 - Eom, Jaemin; Jeon, Kyuheum; Park, Jung Sun; Kang, Yong-Kook (Frontiers in Cell and Developmental Biology, 2022)
SETDB1 is a histone H3-lysine 9-specific methyltransferase that fulfills epigenetic functions inside the nucleus; however, when overexpressed, SETDB1 majorily localizes in the cytoplasm. SETDB1 has a single nuclear-localization-signal (NLS) motif and two successive nuclear-export-signal (NES1 and NES2) motifs in the N-terminus, suggesting that SETDB1 localization is the consequence of a balance between the two antithetic motifs. Here, we performed a series of motif deletions to characterize their effects on the cellular movement of SETDB1. Given the cytoplasmic localization of GFP-SETDB1 in the whole form, without the NES motifs, GFP-SETDB1 was not nuclear, and 3xNLS addition plus NES removal held the majority of GFP-SETDB1 within the nucleus. The results indicated that the cytoplasmic localization of GFP-SETDB1 is the combined result of weak NLS and robust NESs. In ATF7IP-overexpressing cells, GFP-SETDB1 entered the nucleus only in the presence of the NES1 motif; neither the NES2 nor NLS motif was necessary. Since subcellular fractionation results showed that ATF7IP was nuclear-only, an intermediary protein may interact specifically with the NES1 motif after stimulation by ATF7IP. When GFP-SETDB1 had either NES1 or NES2, it was precipitated (in immunoprecipitation) and colocalized (in immunofluorescence) with ATF7IP, indicating that GFP-SETDB1 interacts with ATF7IP through the NES motifs in the nucleus. The regulated nuclear entry of SETDB1 is assumed to set a tight restriction on its abundance within the nucleus, thereby ensuring balanced nuclear SETDB1 levels.